Histopathological study of lupus nephritis with special reference to nonlupus nephritis, focal segmental glomerulosclerosis, interstitial nephritis, and amyloidosis - Usha Singh; Chhaya Rani Shevra; Rana Gopal Singh; Jai Prakash; Shivendra Singh; Nand Kumar Singh (Wolters Kluwer Medknow Publications, 2016)
Context: Lupus nephritis (LN) is the involvement of kidney in systemic lupus erythematosus (SLE) where various types of glomerulonephritis (GN) are seen which affects the therapy also. Aims: To find out the frequency of various types of LN and nonlupus lesion in the kidney of SLE patient. Settings and Design: Retrospective analysis. Subjects and Methods: Total 52 cases of LN were studied between the periods of January 2011 and June 2014. Statistical Analysis Used: Calculation of mean and standard deviation. Results: There was female (76.93%) predominance over males (23.08%). In 63.46%, both ANA and dsDNA antibodies were positive. Only 57.69% patient had typical features of SLE and 17.29% patient had only one clinical manifestation to suggest SLE. In rest cases, renal limited SLE with severe anemia was found. Type IV LN was more common (53.84%) while Type III LN, Type II LN, and Type V LN were seen in equal frequency (9.61% each). In 2 cases, a combination of Type V + IV was found. In 5 cases (9.61%), nonlupus type of lesion was seen. It included 2 cases (3.84%) of amyloidosis and 3 cases of severe chronic tubulointerstitial nephritis with focal segmental glomerulosclerosis (5.76% FSGS). Out of 28 cases of Type IV LN, crescentic GN was found in 10 cases (19.23% CGN). In another 44.44% cases, focal crescents were seen in <40% glomeruli. Conclusions: Thus our study concludes that in LN Type IV is the most common LN and nonlupus related lesions, e.g., amyloidosis, and chronic interstitial nephritis and FSGS can also be found in LN.